Contribution of fracture healing in paediatric DMP zone fracture patients using the pry lever technique - Jingyuan Zhang; Hong Cao (Frontiers Media S.A., 2024)
BackgroundThis study describes the efficacy of applying the prying lever technique to distal radial metaphyseal symphysis diaphysis joining region (DMP) fractures in children, and reports that the technique has an ameliorative effect on the phenomenon of delayed healing and non-union that occurs after surgery for fractures in the DMP region.MethodsThe medical records of 72 children with fractures in the DMP region, treated between December 2017 and December 2023, were retrospectively analyzed. The patients were randomly assigned to either the cut-and-displace group (n = 36) or the pry-and-lever group (n = 36). Both groups were monitored for time to fracture healing, incidence of delayed or non-union, radiologic outcomes, complications, and functional assessments using the EQ-5D, DASH, and VAS scales.ResultsThe follow-up period ranged from 3 to 5 years, with a mean of 26.5 months. After 6 months of follow-up, the incidence of delayed/non-union of fractures was 2.7% and 16.6% in the study and control groups, respectively, and the incidence of delayed healing was significant (P < 0.05) in both groups. Additional manipulations or complications caused by delayed healing or non-union were also significantly less in the study group than in the control group. The EQ-5D scale was used to compare the level of surgical satisfaction between the two groups, and the study group had a higher level of satisfaction. Carpal function was significantly improved in both groups compared to the preoperative period, scored using the DASH scale (P > 0.05). Postoperative pain level was scored using VAS (P < 0.05).ConclusionThe prying lever technique has the advantages of low impact on periosteal blood supply, simple operation, and fast recovery, which makes it a worthwhile attempt of minimally invasive reduction of fractures in the DMP region in children.